2022
DOI: 10.30659/e.7.1.16-31
|View full text |Cite
|
Sign up to set email alerts
|

Reading intensively: What do the students really need?

Abstract: Intensive reading plays a great role in enhancing students� reading comprehension. Effective teaching materials are the best assistance for students. Often, in intensive reading class, lecturers neglected the students� needs and preferences regarding the reading texts and topics being discussed. The materials only come from the lecturers� perspectives. This study explores the students' needs and lecturers' perceptions toward the effective teaching materials of intensive reading. A questionnaire, delivered to 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 15 publications
(25 reference statements)
1
2
0
Order By: Relevance
“…Furthermore, the researchers allowed the students to choose the text they wanted to read for extensive reading, which can make the students more interested in reading the text. A similar result was also seen in [15]; they said that increasing the pupils' enthusiasm for reading can contribute to the development of a positive environment in the reading classroom. Regarding the impact of strategy-based instruction on students' reading comprehension, data obtained from the pretest and posttest showed that the average student score was 73, while the posttest score was 81.…”
Section: Discussionsupporting
confidence: 57%
“…Furthermore, the researchers allowed the students to choose the text they wanted to read for extensive reading, which can make the students more interested in reading the text. A similar result was also seen in [15]; they said that increasing the pupils' enthusiasm for reading can contribute to the development of a positive environment in the reading classroom. Regarding the impact of strategy-based instruction on students' reading comprehension, data obtained from the pretest and posttest showed that the average student score was 73, while the posttest score was 81.…”
Section: Discussionsupporting
confidence: 57%
“…The study of Andres (2020), to illustrate, has aimed at improving students' reading comprehension through intensive reading activities. Similar study has been also conducted by Ni'mah and Sholihah (2022) but by considering the needs of students. Another study has been carried out by Moon and Kwan (2022) but by positioning students' intensive reading skill as the target rather as the method.…”
Section: Introductionmentioning
confidence: 87%
“…Andres (2020) reveals that the purpose of intensive reading is not only to obtain the information but also the grammatical features. According to Ni'mah and Sholihah (2022), the activities of intensive reading are divided into pre-reading, while-reading, and post-reading. They further elaborate that in intensive reading students are directed to various genres of texts.…”
Section: Introductionmentioning
confidence: 99%